2017
DOI: 10.3389/fict.2017.00016
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of the Benefits of an Animallike Robot Companion with More Advanced Touch Interaction Capabilities for Dementia Care

Abstract: Animallike robot companions such as robotic seal Paro are increasingly used in dementia care due to the positive effects that interaction with these robots can have on the well-being of these patients. Touch is one of the most important interaction modalities for patients with dementia and can be a natural way to interact with animallike robots. To advance the development of animallike robots, we explored in what ways people with dementia could benefit from interaction with an animallike robot with more advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 39 publications
5
59
0
Order By: Relevance
“…The initial searches identified 2,931 unique papers. Of these, 344 were selected for full‐text review and 19 studies (reported in 27 papers) met the inclusion criteria (see Figure for reasons for exclusion): 10 qualitative studies (Birks, Bodak, Barlas, Harwood, & Pether, ; Chang & Sabanovic, ; Chang, Sabanovic, & Huber, ; Giusti & Marti, ; Gustafsson, Svanberg, & Müllersdorf, ; Iacono & Marti, ; Jung, van der Leij, & Kelders, ; Moyle et al, ; Niemelä, Määttä, & Ylikauppila, ; Pfadenhauer & Dukat, ), 2 mixed methods (randomised trials with qualitative elements), reported across 8 papers (Mervin et al, ; Moyle, ; Moyle, ; Moyle, ; Moyle, ; Moyle, ; Robinson, Macdonald, Kerse, & Broadbent, , ) and seven randomised trials reported in nine papers (Banks, Willoughby, & Banks, ; Joranson, Pedersen, Rokstad, & Ihlebaek, , ; Libin & Cohen‐Mansfield, ; Moyle et al, ; Petersen, Houston, Qin, Tague, & Studley, ; Thodberg, Sorensen, Christensen, et al, ; Thodberg, Sørensen, Videbech, et al, ; Valenti Soler et al, ). An update search, carried out in July 2018 across all databases with de‐duping against those already screened, found no additional included papers or studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The initial searches identified 2,931 unique papers. Of these, 344 were selected for full‐text review and 19 studies (reported in 27 papers) met the inclusion criteria (see Figure for reasons for exclusion): 10 qualitative studies (Birks, Bodak, Barlas, Harwood, & Pether, ; Chang & Sabanovic, ; Chang, Sabanovic, & Huber, ; Giusti & Marti, ; Gustafsson, Svanberg, & Müllersdorf, ; Iacono & Marti, ; Jung, van der Leij, & Kelders, ; Moyle et al, ; Niemelä, Määttä, & Ylikauppila, ; Pfadenhauer & Dukat, ), 2 mixed methods (randomised trials with qualitative elements), reported across 8 papers (Mervin et al, ; Moyle, ; Moyle, ; Moyle, ; Moyle, ; Moyle, ; Robinson, Macdonald, Kerse, & Broadbent, , ) and seven randomised trials reported in nine papers (Banks, Willoughby, & Banks, ; Joranson, Pedersen, Rokstad, & Ihlebaek, , ; Libin & Cohen‐Mansfield, ; Moyle et al, ; Petersen, Houston, Qin, Tague, & Studley, ; Thodberg, Sorensen, Christensen, et al, ; Thodberg, Sørensen, Videbech, et al, ; Valenti Soler et al, ). An update search, carried out in July 2018 across all databases with de‐duping against those already screened, found no additional included papers or studies.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were conducted within the past 15 years. Five studies were conducted in the United States (Banks et al, ; Birks et al, ; Chang & Sabanovic, ; Chang et al, ; Petersen et al, ) and four in Australia (Birks et al, ; Moyle et al, , , ), with the remaining studies taking place in Italy (Giusti & Marti, ; Iacono & Marti, ), New Zealand (Robinson, Macdonald, Kerse, & Broadbent, ), Denmark (Thodberg, Sorensen, Christensen, et al, ), Finland (Niemelä et al, ), Germany (Pfadenhauer & Dukat, ), the Netherlands (Jung et al, ), Norway (Joranson, Pedersen, Rokstad, & Ihlebaek, ), Spain (Valenti Soler et al, ) and Sweden (Gustafsson et al, ). The studies involved more than 800 residents (the total number is not clear as two observation studies did not report the number of residents observed) (Chang & Sabanovic, ; Pfadenhauer & Dukat, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations